Public Services Analysis in Manufacturing E-KTP Didistrict Population and Civil Registration Officeprophet of 2021 – 2022 - Octofianus Karubaba; Dede Sri Kartini; Widya Setiabudi Sumadinata (Budapest International Research and Critics University, 2022)
The purpose of this study (1) is to find out the process of Public Service in Making E-KTP at the Department of Population and Civil Registration of Nabire Regency in 2021-2022. The result is that public services in making E-KTP at the Nabire Regency Population and Civil Registration Office in 2021-2022 have not been maximized in the tangible dimension, because technical implementation has experienced several problems such as: slow application response, unavailability of blanks, takes a long time, damaged equipment. recorders, officers have not carried out their work thoroughly and on time, slow service, lack of employees, and dependence on server networks. In the dimension of reliability, Disdukcapil officers serve as well as expertise in operating and overcoming problems with assistive devices, which are very good and supported by clear service standards. In the responsiveness dimension, the Disdukcapil of Nabire Regency provides the response that the community needs quickly and responsively. In the assurance dimension, the Disdukcapil of Nabire Regency provides a guarantee of service time with certainty of service time and certainty of getting good service. While on the empathy dimension, the Disdukcapil officer of Nabire Regency puts the interests of the applicant first, being friendly and polite and not discriminatory by applying the 5S culture, namely Smile, Greeting, Greet, Polite and Courteous in the e-KTP service process.